Religious coping of Malaysian Muslims with high Sensory-Processing Sensitivity in facing the loss of loved one(s) - Nurul Insyirah Indera Luthfi; Intan Aidura Alias; Mardiana Mohamad (SIMULACRA: JURNAL SOSIOLOGI, 2023)
Sensory-Processing Sensitivity (SPS) characterizes people’s characteristic sensitivity to experience. SPS is a young field of research. There are limitations in the study of SPS and religiosity and spirituality. This study seeks to explore how Muslims with high SPS view the loss they have experienced and how they cope with the loss from an Islamic perspective. Interpretative Phenomenological Analysis (IPA) was used as the method of the study to allow for an in-depth exploration of how participants make sense of their loss experiences. The study recruited five high SPS Malaysian Muslims to explore the loss and coping experiences they had during the COVID-19 crisis and how they viewed the experiences in Islamic perspectives. The study found three themes in the application of Islamic perspectives in viewing the loss experienced by the participants and the way they coped with the loss. The Malaysian Muslim participants applied Islamic teachings as protective and therapeutic aspects to cope with the loss of loved ones, which is consistent with previous studies on Islamic religiosity. It is recommended that future SPS studies focus on exploring how individuals with different levels of SPS view religiosity and spirituality aspects of life events, especially within the Malaysian Muslim community.